The effectiveness of honey for the management of radiotherapy-induced oral mucositis in head and neck cancer patients: a systematic review of clinical trials - Charalampous, Melanie; Charalambous, Andreas; Raftopoulos, Vasilios; Lambrinou, Ekaterini (My University, 2013)
Aim: To evaluate the effectiveness of honey in the management of oral mucositis in head and neck cancer patients undergoing radiotherapy. Methods: The review of the literature was based on a keyword strategy and pre-determined inclusion and exclusion criteria. The keywords “head and neck cancer”, “radiotherapy”, “oral mucositis”, “controlled trial” and “honey” were used as search terms in the EMBASE, CINAHL, COCHRANE and PUBMED databases. The citation and reference list of the eligible articles were also screened for potentially relevant articles. The methodological quality of the selected trials was assessed by the JADAD scale. Results: In total, 5 studies met the criteria and were included in the systematic review. Three studies assessed the effectiveness of honey against other productsincluding golden syrup, lignocaine and saline and two studies assessed the effectiveness of honey againststandard treatment regimes. Four out of the five studies demonstrated significant reduction in the mucositislevels and one study reported that honey had no statistical association with less severe mucositis. Methodologically the quality of most studies was moderate due to the small sample size, which might impact upon the significance of the findings. Conclusions: Although honey appears to be a simple, affordable, available and cost-effective treatment for the management of radiation-induced oral mucositis, there is a need for further multi-centre randomized trials to validate these findings.
Keywords: Clinical trials; Honey; Oral mucositis; Radiation therapy; Head and neck cancer